59‐6: Directed Electrostatic Microassembly for MicroLED Display. Issue 1 (28th June 2021) - Rupp, Bradley B.; Crawford, Lara S.; Lu, Jeng Ping; Plochowietz, Anne; Biegelsen, Dave; Raychaudhuri, Sourobh; Butylkov, Sergey; Wang, Yunda; Chow, Eugene M.
Abstract : We are developing a new chip integration tool based on massively parallel deterministic sorting and assembly, aiming to achieve the low cost of printing with the control of pick and place. Such a tool would enable scalable microLED display manufacturing and heterogeneous integration for advanced functionality. We describe a prototype system demonstrating continuous line by line assembly, and report single chip speed measurements of a centimeter per second, suggesting the approach could eventually support high throughput.